Other Rhythms in Schools on the Outskirts of São Paulo - Alexandre Barbosa Pereira (Universidade Federal do Rio Grande do Sul, 2015)
The paper discusses research carried out in public schools on the outskirts of São Paulo in order to understand the development of youth sociability. The proposal is to describe the dimensions that the youth category acquires from the students' experiences. Students engender rhythms in conflict with the rhythm of discipline. Through the new technologies and mass culture, they have taken part in other activities and have constituted specific publics formed prior to and out of the school. Thus, if the school tries to isolate itself from the outside world with gates and bars, young people with their different rhythms, mainly that of banter, introduce in the school the most different and singular worlds.